2020
DOI: 10.3390/antiox9080653
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Obesity- and Type 2 Diabetes-Induced Heart Failure

Abstract: Obesity is a risk factor for the development of type 2 diabetes (T2D), which is associated with cardiovascular diseases [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Indeed, previous studies have suggested that various pathologic conditions, such as toxins, medications, hypertension, diabetes, and obesity, might trigger cardiomyocyte autophagy and apoptosis, cause disordered cardiac structure, and then lead to cardiac dysfunction [44][45][46][47]. Therefore, our findings will provide a new perspective and novel therapeutic targets for effectively alleviating myocardial injury.…”
Section: 4mentioning
confidence: 59%
“…Indeed, previous studies have suggested that various pathologic conditions, such as toxins, medications, hypertension, diabetes, and obesity, might trigger cardiomyocyte autophagy and apoptosis, cause disordered cardiac structure, and then lead to cardiac dysfunction [44][45][46][47]. Therefore, our findings will provide a new perspective and novel therapeutic targets for effectively alleviating myocardial injury.…”
Section: 4mentioning
confidence: 59%
“…Catalase (CAT) is a key enzyme that decomposes hydrogen peroxide into water and oxygen, serving as a major component of the cellular antioxidant defense system [ 46 ]. Oxidative stress leads to an increase in hydrogen peroxide levels.…”
Section: Resultsmentioning
confidence: 99%
“…In chronic heart failure, myocardial injury, ventricular remodeling, and alterations in mitochondrial structure and number occur, leading to a shift in myocardial metabolism from fatty acids to glucose, decreased glucose oxidation, and increased glycolysis [ 46 ]. TG hydrolysis, one of the pathways for free fatty acid production, decreases after heart failure, leading to increased serum levels [ 46 ]. The study suggests that crocetin can regulate lipid and energy metabolism to some extent and promote angiogenesis, increasing oxygen supply and further powering myocardial contraction.…”
Section: Discussionmentioning
confidence: 99%
“…The redox imbalance can be consequential on various diseases, like metabolic syndrome, obesity, diabetes, cancer, etc (38,39). The potency of exogenous antioxidants is assessed biochemically by measuring the reducing power and percentage inhibition of oxidative stressors (i.e., free radicals).…”
Section: Discussionmentioning
confidence: 99%